The prognostic significance of incomplete hematological recovery in pediatric patients with low/intermediate risk AML and negative MRD after induction 1 - Shahin, Nessma M.; Hammad, Mahmoud; Hafez, Hanafy; Salem, Sherine; El-Sharkawy, Nahla; Elnashar, Amr; Lehmann, Leslie; El-Haddad, Alaa (Frontiers in Oncology, 2025)
BackgroundPediatric acute myeloid leukemia (AML) accounts for approximately 25% of childhood hematologic malignancies. Outcomes have markedly improved, especially in low-risk and intermediate-risk patients, with overall survival (OS) rates approaching 80–85%. Prognosis is primarily determined by cytogenetic/molecular risk and minimal residual disease (MRD) status following induction therapy. While complete remission (CR) traditionally requires morphologic clearance of leukemia with full hematologic recovery, some patients achieve morphologic remission with incomplete recovery (CRi). Although adult studies associate CRi with poor prognosis, its relevance in MRD-negative pediatric AML remains unclear. This study evaluates the prognostic significance of hematologic recovery in MRD-negative, low/intermediate-risk pediatric AML.MethodsWe conducted a retrospective analysis of 120 pediatric AML patients treated at CCHE-57357 between 2012 and 2020 who achieved MRD negativity (<0.1% by 8–10 color flow cytometry) after Induction I. Risk stratification followed WHO/ELN guidelines. For exploratory purposes, intermediate-risk patients with MRD <0.1% were reclassified as “MRD-defined low risk.” Patients were categorized by hematologic recovery: CR (ANC ≥1000/µL, platelets ≥100,000/µL), partial hematological recovery (CRh) (ANC ≥500/µL and/or platelets ≥50,000/µL), and CRi (ANC 500/µL and/or platelets <50,000/µL). Outcomes included OS, relapse-free survival (RFS), and event-free survival (EFS).ResultsAmong 120 patients (median age 8.5 years), 25 (21%) achieved CR, 17 (14.3%) CRh, and 78 (64.7%) CRi. CRi patients had numerically lower 5-year OS (63.3%) compared to CRh (76%) and CR (71.8%), though differences were not statistically significant. Platelet recovery alone (complete Platelet recovery (CRp) vs incomplete platelet recovery (CRip) showed a trend toward prognostic relevance (5-year OS: 73.3% vs 57.1%), also non-significant. Infectious complications were common: six sepsis-related deaths occurred in the low-risk group and four in the standard-risk group, with ICU admissions disproportionately higher in standard-risk patients (12 vs 1). CRi patients experienced longer hospital stays and required more transfusion support.ConclusionIn MRD-negative pediatric AML, incomplete hematologic recovery did not significantly predict inferior survival, though trends suggest potential prognostic value—particularly in low-risk patients. CRi may reflect treatment-related toxicity or infectious complications rather than residual disease. These findings support a more nuanced interpretation of remission depth and highlight the need for larger, multi-institutional studies incorporating molecular risk refinement and clinical context.